2004
DOI: 10.1074/jbc.m306066200
|View full text |Cite
|
Sign up to set email alerts
|

hXRCC2 Enhances ADP/ATP Processing and Strand Exchange by hRAD51

Abstract: The assembly of bacterial RecA, and its human homolog hRAD51, into an operational ADP/ATP-regulated DNA-protein (nucleoprotein) filament is essential for homologous recombination repair (HRR). Yet hRAD51 lacks the coordinated ADP/ATP processing exhibited by RecA and is less efficient in HRR reactions in vitro. In this study, we demonstrate that hXRCC2, one of five other poorly understood non-redundant human mitotic RecA homologs (hRAD51B, hRAD51C, hRAD51D, hXRCC2, and hXRCC3), stimulates hRAD51 ATP processing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 59 publications
(66 reference statements)
4
32
0
Order By: Relevance
“…Intriguingly, Bugreev et al (2007b) show that BLM is only able to disrupt inactive hRad51 filaments present in an ADP-bound form. It was previously shown that ATP hydrolysis leads to spontaneous hRad51 filament inactivation (Bugreev and Mazin 2004) and that some auxiliary proteins may help to maintain the filament in an active form (Shim et al 2004), thus corroborating the idea that hRad51 displacement by BLM occurs if the cells are not fully prepared for the later steps of HR. In this situation, the hRad51 filaments may remain inactive and susceptible to BLM dissociation.…”
Section: Similarities and Dissimilarities Between Blm Recql5 And Srs2supporting
confidence: 55%
“…Intriguingly, Bugreev et al (2007b) show that BLM is only able to disrupt inactive hRad51 filaments present in an ADP-bound form. It was previously shown that ATP hydrolysis leads to spontaneous hRad51 filament inactivation (Bugreev and Mazin 2004) and that some auxiliary proteins may help to maintain the filament in an active form (Shim et al 2004), thus corroborating the idea that hRad51 displacement by BLM occurs if the cells are not fully prepared for the later steps of HR. In this situation, the hRad51 filaments may remain inactive and susceptible to BLM dissociation.…”
Section: Similarities and Dissimilarities Between Blm Recql5 And Srs2supporting
confidence: 55%
“…The human Xrcc2 protein enhances ADP/ATP processing by human Rad51, resulting in more-efficient strand exchange (44). Although no stimulation of Rad51 ssDNA binding by Xrcc2 was observed, the Rad51 filament might be more dynamic in vivo, requiring multiple cycles of binding and release in order to form an active presynaptic filament.…”
Section: Discussionmentioning
confidence: 97%
“…1A). The human RAD51 paralogs have been purified in a variety of heteromeric forms (9,10,12,46). However, the quantities of these heteromeric forms and their tendency to aggregate have thus far inhibited a complete examination of their biophysical and structural role in HR.…”
Section: Discussionmentioning
confidence: 99%